2013
DOI: 10.3344/kjp.2013.26.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Erythromelalgia - A Case Report -

Abstract: Erythromelalgia is a rare neurovascular pain syndrome characterized by a triad of redness, increased temperature, and burning pain primarily in the extremities. Erythromelalgia can present as a primary or secondary form, and secondary erythromelalgia associated with a myeloproliferative disease such as essential thrombocythemia often responds dramatically to aspirin therapy, as in the present case. Herein, we describe a typical case of a 48-year-old woman with secondary erythromelalgia linked to essential thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…The term ‘erythermalgia’ in the past has been used interchangeably with ‘erythromelalgia’, while some authors have used erythromelalgia for the aspirin‐responsive disease and erythermalgia for the aspirin‐resistant disease . Unfortunately, the term ‘primary erythromelalgia’ is sometimes still used to indicate idiopathic erythromelalgia …”
Section: Terminology and Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The term ‘erythermalgia’ in the past has been used interchangeably with ‘erythromelalgia’, while some authors have used erythromelalgia for the aspirin‐responsive disease and erythermalgia for the aspirin‐resistant disease . Unfortunately, the term ‘primary erythromelalgia’ is sometimes still used to indicate idiopathic erythromelalgia …”
Section: Terminology and Classificationmentioning
confidence: 99%
“…Primary erythromelalgia tends to have a younger age of onset in comparison with secondary disease, presenting in the first decade of life, in contrast to a median onset of 49.1 years pain, which is often the most prominent and disabling feature of the condition, can vary between individuals; it may start as a mild burning or itching sensation and progress to a severe burning sensation . Some case reports have observed that the pain tends to start quite suddenly, and can increase in severity and frequency with time . However, the pain, along with the other symptoms, tends to occur intermittently, thus making diagnosis more challenging if presentation to a clinician is at a time of quiescence …”
Section: Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermography does not have the benefit of knowing the signal source, because it is [180] 2013 2a 1 ---Arita et al [181] 2013 2a 1 ---Purslow [182] 2013 1a 1 ---Klamann et al [183] 2013 2a 1 ---Petznick et al [184] 2013 2a 1 ---Gonnermann et al [178] 2012 2a 1 ---Kottaiyan et al [185] 2012 2a 1 ---Tan et al [186] 2011 4a 1 ---Kamao et al [187] 2011 2a 2 -83 80 Tan et al [188] 2010 4a 1 ---Tan et al [189] 2010 3a 1 ---Tan et al [190] 2010 2a 1 ---Acharya et al [191] 2009 4a 1 ---Chiang et al [192] 2006 2a 2 -79.3 75 Purslow et al [193] 2005 2a 2 ---Cherkas et al [194] 2003 2a 1 ---Morgan et al [195] 1999 1a ----Mori et al [196] 1997 1a 1 ---Morgan et al [197] 1996 2a 1 ---Morgan et al [198] 1995 2a 1 --- Table 6: Pain and inflammation diagnosis results. Authors Year MP PE A (%) Se (%) Sp (%) Jeong et al [203] 2013 2b ----Dibai Filho et al [204] 2013 1b 1 ---Kang et al [202] 2013 2b ----Rodrigues-Bigaton et al [88] 2013 1a 2 -62.2 75.6 Dibai Filho et al [205] 2013 1a 2 60 55.8 55.8 Zaproudina et al [206] 2013 2a 1 ---Roy et al [207] 2013 2a 1 ---Choi et al [201] 2013 2b 1 ---Zaproudina et al [208] 2013 2a 1 ---Frize and Ogungbemile [209] 2012 3b 3 -96 92 Hildebrandt et al [210] 2012 2b ----Laino [211] 2012 2b ----Wu et al [212] 2009 2b 1 ---Chang et al [213] 2008 1b 1 ---Niehof et al [214] 2007 2a 2 -74.3 83.9 Park et al …”
Section: Discussionmentioning
confidence: 99%
“…IRT can help medical practitioners to detect areas of cutaneous thermal changes of neural origin and it can lead to a high degree of interexaminer agreement for assessing skin temperature differences in patients with CRPS [200,201]. Kang et al show that IRT can be used in the diagnosis and assessment of therapeutic results for erythromelalgia [202]. Table 6 details the work published on CAD systems for pain detection.…”
Section: Pain and Inflammationmentioning
confidence: 99%